Gold Micro-Shunt Implants Versus Ahmed Glaucoma Valve: Long-term Outcomes of a Prospective Randomized Clinical Trial. Issue 2 (February 2016) - Skaat, Alon; Sagiv, Oded; Kinori, Michael; Simon, Guy J. Ben; Goldenfeld, Modi; Melamed, Shlomo
Abstract : Purpose: To compare long-term outcomes of Ahmed glaucoma valve (AGV), 24 μm Gold Micro-Shunt (GMS), and 48 μm GMS implantation for treatment of refractory glaucoma. Patients and Methods: This was a 3-armed randomized interventional prospective clinical trial. Within an institutional setting, 29 adults (29 eyes) with refractory glaucoma [mean baseline intraocular pressure (IOP) ≥22 mm Hg on maximal medication, status post at least 1 failed trabeculectomy, defined visual field defect, and without recent glaucoma-related surgery] were randomly assigned to AGV, 24 μm GMS, or 48 μm GMS implantation. Exclusion criteria included uveitic, traumatic, or neovascular glaucoma. The 3 groups were comparatively evaluated preoperatively and 1, 2, 3, and 5 years postoperatively for IOP and numbers of glaucoma medications needed. Main outcome measures were implant survival rates. Results of the 24 and 48 μm GMS groups were also compared separately. Results: In all groups the final IOP (in mm Hg) was significantly lower than the preoperative IOP (17.3±2.6 vs. 33.5±6.7, P =0.004; 17.8±2.4 vs. 25.7±0.7, P =0.0001; and 19.6±5.2 vs. 35.6±2.2, P =0.0001 in the AGV, 24 μm GMS, and 48 μm GMS groups, respectively). Differences between initial and final mean numbers of medications were not significant. Cumulative probabilities of success at 5 years were 77.8%, 77.8%, and 72.7%, respectively. Conclusions: During long-term follow-up, success rates in the 2 GMS groups and the AGV group were similar. Likewise, IOP reduction and the need for continued glaucoma medical therapy remained high and were similar for all devices.